Human understanding: filosophical and legal dimension - Бородін, Іван Лук’янович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Democratic changes in Ukraine impose new demands on the determination of human rights and freedoms. The understanding of a human on the basis of high standards of a civilized society is possible in case of a decent attitude to a person, strengthening of the protection of human rights and freedoms, different forms of property and other priorities of a legal, democratic society, defined by the Constitution of Ukraine. The achievement of these goals involves bringing the regulatory framework to European standards, taking into account the achievements of scientists from Ukraine and other countries associated with the problem of philosophical and legal human dimension.